Traumatic hand reconstruction: modern surgical approaches and decision-making - Toledo, Yosuany R. G.; Gaviño, Urías Z. (International Surgery Journal, 2026)
Traumatic hand injuries represent a complex reconstructive challenge due to the need to restore function, sensibility, and aesthetic appearance simultaneously. Injury patterns range from isolated fingertip loss to severe crush, avulsion, and blast trauma, requiring individualized and often staged surgical strategies. Contemporary traumatic hand reconstruction emphasizes algorithmic decision-making based on defect location, size, and exposed structures, guiding the selection from skin grafts and local flaps to regional and free tissue transfer. Core surgical principles include meticulous debridement, skeletal stabilization, vascular repair when indicated, and early provision of stable soft-tissue coverage, followed by secondary reconstruction of tendons, nerves, and bone as needed. Microsurgical techniques, including thin free flaps and toe-to-hand transfers, have become central in the management of complex defects, demonstrating high survival rates and meaningful functional recovery in both adult and pediatric populations. Increasing attention to aesthetic–functional balance, donor-site morbidity, and structured rehabilitation has further improved long-term outcomes. This state-of-the-art review summarizes current principles, algorithms, and evolving surgical approaches in traumatic hand reconstruction.